Drivers of Recurring Seasonal Cycle of Glacier Calving Styles and Patterns - Kneib-Walter, Andrea; Lüthi, Martin P.; Moreau, Luc; Vieli, Andreas (Frontiers in Earth Science, 2021)
Calving is a crucial process for the mass loss of outlet glaciers in Greenland, while at the same time the calving contributes to large uncertainties in current glacier flow models and projections, particularly due to a lack of observations. Here we investigate the frequency, volume and style of calving events by using high-resolution terrestrial radar interferometer data from six field campaigns, continuous daily and hourly time-lapse images over six years and 10-second time-lapse images recorded during two field campaigns. The results demonstrate that the calving front of Eqip Sermia, a fast flowing, highly crevassed outlet glacier in West Greenland, follows a clear seasonal cycle showing a distinct pattern in areas with subglacial discharge plumes, shallow bed topography and during the presence and retreat of proglacial ice mélange. Calving event volume, frequency and style vary strongly over time depending on the state in the seasonal cycle. Strong spatial differences between three distinctive front sectors with differing bed topography, water depth and calving front slope were observed. A distinct increase in calving activity occurs in the early melt season simultaneously when ice mélange disappears and meltwater plumes become visible at the fjord surface adjacent to the ice front. While reduced retreat of the front is observed in shallow areas, accelerated retreat occurred at locations with subglacial meltwater plumes. With the emergence of these plumes at the beginning of the melt season, larger full thickness calving events occur likely due to undercutting of the calving front. Later in the melt season the calving activity at subglacial meltwater plumes is similar to the neighboring areas, suggesting the presence of plumes to become less important for calving. The results highlight the significance of subglacial discharge and bed topography on the front geometry, the temporal variability of the calving process and the variability of calving styles.